Experimental investigation on mechanical behaviour and parameters of FDM printed carbon fibre reinforced PET-G and PET-G - Dakhil Jasym, Kareem (International Journal of Engineering and Technology, 2019)
In present study tests like Tensile, Compression and Flexural on the 3D Printed standard specimens of PETG and CARBON FIBER REINFORCED is carried on PETG by changing the printing parameters to find their mechanical properties by using FDM. The experimental results indicated that the tensile strength of carbon fiber reinforced pet-G is 1.28% higher than pure PET-G sample. Its optimum value is observed from Taguchi L9 to be 30.804 from SN curve and same as 34.629 in MEAN curve. The variation in the two values is noticed to be 12.12 % for SN curve and 0 % in case of MEANS Carbon fiber PET-G specimen with 300µ layer thickness, 80% infill density, 60 mm/sec print speed had the largest mean value of tensile strength. The ultimate tensile strength of fabricated specimen with 300µ layer thickness, 80% infill density, and 60 mm/sec print speed could increase 1.28% when compared with pure PET-G specimen.